Analysis of Methods and Sources of Interpretation of the Book of Tafsir Al Kasyif in Surah Al Fatihah Verses 1-7 - Edi; Sigit Abdulloh; Eni Zulaiha; Wildan Taufiq (al-Afkar, Journal For Islamic Studies, 2026)
Interpretation as a result or product of the dialectic between the reasoning of an interpreter and the text, and the context that surrounds it, requires continuous dynamics, interpretation has no stopping point. That is why the product of interpretation needs to be studied. This writing aims to analyze the methods and sources of interpretation used in the book Tafsir al Kasyif by Muhammad Jawwad Mugniyah, especially in surah al Fatihah verses 1-7. The author uses a qualitative method through literature study with various reference sources, both primary and secondary based on books, journals, and others that support this research. The special methods presented by Tafsir al Kasyif include: presenting a special discussion on Isti'adzah and Basmallah; mentioning the name of the surah; writing one surah as a whole; presenting various opinions about where it was revealed; explaining the naming of surah al Fatihah first; Interpreting the Qur'an verse by verse; explaining the rules of language; explaining the meaning and prioritizing the opinion of Ali Zainal Abidin; Explaining vocabulary; explaining the differences in readings (qiraat). Muhammad Jawwad uses a general method: Tahlili, in presenting his tafsir work, along with a special method that tends towards linguistic rules to examine each meaning, and is accompanied by a variety of opinions that prioritize opinions oriented towards the fanaticism of his sect's ideology. If there are differences in readings or qiraat, he presents these differences, but does not explain them in depth and includes strong sources, only as informative.